Universal Humanitarian Principles Of Minangkabau Proverbs: A Living Law Perspective - Rusman, Rina; Daulay, Zainul; Danil, Elwi; Sofyan, Syofirman (Publikasi Indonesia, 2023)
Difference from other studies that discuss proverbs from the perspective of art and linguistic, this study focused on its’ relevance with universal humanitarian principles adopted in various international treaties of international humanitarian and human rights laws. This study was conducted because several important treaties are not yet ratified by Indonesia due to an assumption that there are certain principles are not align with the living law in Indonesia. Even, the State needs to invoke certain provisions from the treaties to persuade the protection of its citizens being abroad whom trapped in situations of armed conflict and other situations of violence. This study answers this following question: Do Minangkabau proverbs provide sufficient relevant values which are align with the universal humanitarian principles? This research used the living law perspective and legal normative method in finding the relevant proverbs. The research result shows that the universal humanitarian principles can be found in certain relevant proverbs. At least 40 Minangkabau proverbs are compatible with and cover the ten universal humanitarian principles discussed. It proves that, from the cultural view, Indonesia is ready to ratify the certain main international treaties.